In vitro and in vivo characterization of temoporfin-loaded PEGylated PLGA nanoparticles for use in photodynamic therapy. (May 2012) - Rojnik, Matija; Kocbek, Petra; Moret, Francesca; Compagnin, Chiara; Celotti, Lucia; Bovis, Melissa J; Woodhams, Josephine H; MacRobert, Alexander J; Scheglmann, Dietrich; Helfrich, Wijnand; Verkaik, Marco J; Papini, Emanuele; et al.
Aims: In this study we evaluated temoporfin-loaded polyethylene glycol (PEG) Poly-(D, L -lactide-co-glycolide) (PLGA) nanoparticles (NPs) as a new formulation for potential use in cancer treatment.Materials & methods: NPs were characterized for their photophysical properties, temoporfin release, cellular uptake and intracellular localization, and dark and photocytotoxicities of temoporfin by using A549, MCF10A neoT and U937 cell lines. In vivo imaging was performed on athymic nude-Foxn1 mice.Results: Temoporfin was highly aggregated within the NPs and the release of temoporfin monomers was faster from PEGylated PLGA NPs than from non-PEGylated ones. PEGylation significantly reduced the cellular uptake of NPs by the differentiated promonocytic U937 cells, revealing the stealth properties of the delivery system. Dark cytotoxicity of temoporfin delivered by NPs was less than that of free temoporfin in standard solution (Foscan ®, Biolitec AG [Jena, Germany]), whereas phototoxicity was not reduced. Temoporfin delivered to mice by PEGylated PLGA NPs exhibits therapeutically favorable tissue distribution.Conclusion: These encouraging results show promise in using PEGylated PLGA NPs for improving the delivery of photosensitizers for photodynamic therapy. Original submitted 30 March 2011; Revised submitted 9 July 2011